1995
DOI: 10.1159/000106940
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathological Diagnoses in Elderly Patients in Oslo: Alzheimers Disease, Lewy Body Disease, Vascular Lesions

Abstract: Neuropathological changes in elderly residents of Oslo, Norway, were characterised with respect to the cerebral substrates of dementia. Ninety-two brains were examined, representing 41% of all deaths occurring in 10 nursing homes during a 9-month period. The autopsy cohort showed a similar mean age (85 years) and sex ratio (73% female) and proportion of demented patients (75%) compared to all the patients resident in these homes who died during the same period. Clinical data was compiled retrospectively. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 19 publications
4
42
0
5
Order By: Relevance
“…However, they did not use systematic AS immunohistochemistry for LB detection. [19][20][21][22][23][24][25] Two studies that also used the LB509 antibody reported that approximately 50% of cases with familial AD and Down syndrome with concomitant AD have coexistent LBs. 26,27 Therefore, we anticipate that our observed LB prevalence is comparable with that observed in other AD research centers.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not use systematic AS immunohistochemistry for LB detection. [19][20][21][22][23][24][25] Two studies that also used the LB509 antibody reported that approximately 50% of cases with familial AD and Down syndrome with concomitant AD have coexistent LBs. 26,27 Therefore, we anticipate that our observed LB prevalence is comparable with that observed in other AD research centers.…”
Section: Discussionmentioning
confidence: 99%
“…Dette er ikke uventet. Ifølge nevropatologiske undersøkelser har mange med kliniske demenssymptomer en blanding av ulike demenssykdommer (36). Om lag 75 % av dem med diagnosen nevropatologisk demens med lewylegemer har samtidig nevropatologiske forandringer i hjernen som indikerer en samtidig Alzheimers sykdom (37).…”
Section: Diskusjonunclassified
“…Om lag 75 % av dem med diagnosen nevropatologisk demens med lewylegemer har samtidig nevropatologiske forandringer i hjernen som indikerer en samtidig Alzheimers sykdom (37). Kombinasjon av vaskulaer demens, demens med lewylegemer og demens av Alzheimers type er heller ikke uvanlig (36). Det er mulig at en automatisert MR-analyse ville klart å skille demens av Alzheimers type fra frontotemporal demens, men gruppen med fronttotemporal demens er for liten for å teste denne hypotesen.…”
Section: Diskusjonunclassified
“…Частота ДТЛ среди всех причин деменции составляет от 7 до 30% [8,13,14]. На первых этапах исследования, ве-роятно, имела место как низкая, так и чрезмерная диагно-стика заболевания: в части случаев ДТЛ расценивалась как БА, болезнь Паркинсона (БП) с деменцией, супрануклеар-ный паралич.…”
unclassified
“…По данным некоторых авторов [13,22], ДТЛ чаще страдают мужчины (66% мужчин и 34% женщин) в отличие от БА, которой преимущественно болеют женщины. По мнению других исследователей, не отмечается преобладания того или иного пола.…”
unclassified